Does the ESG Performance Differ Across Sectors? An Insight into the Indian Corporate Landscape - Kanoo, Rishav; Debi, Hiranmayee; Bhuyan, Anil Kumar; Paul, Barnali; Saha, Animesh; Chakravarty, Ekta; Debnath, Pranesh (International Journal of Economics and Financial Issues, 2024)
In the present corporate landscape, the ESG score is a yardstick for corporate sustainability performance. This study compares the ESG score across selected sectors operating in India using cross-sectional data based on 260 top companies by the market capitalization across 26 selected sectors operating in India. Data relating to ESG scores have been taken from CRISIL for the year 2022. Descriptive statistics were employed to summarize the ESG performance across the sectors. Whereas, One-way ANOVA were applied to ascertain significant differences in ESG and sub-dimensional scores across selected sectors. The findings demonstrate that the IT sector recorded the highest score on GOV dimensions, whereas the banking sector outperformed the other sectors in the ENV and SOC dimensional scores and the aggregated ESG score. Moreover, the findings also reveal that polluting sectors, such as the Metals and Chemical sectors, are less responsive towards ESG performance due to their inherent nature of production. Furthermore, ANOVA result reveals a remarkable difference in ESG performance among the selected sectors. This study provides insights for investors to identify socially responsible sectors and offers a wake-up call for regulators and legislators to frame stringent regulations for industries that disregard social, environmental and governance norms.